Global surfaces of section with positive genus for dynamically convex Reeb flows - Hryniewicz, Umberto; Salomão, Pedro A. S.; Siefring, Richard (Journal of fixed point theory and applications, 2022)
We establish some new existence results for global surfaces of section of dynamically convex Reeb flows on the three-sphere. These sections often have genus, and are the result of a combination of pseudoholomorphic methods with some elementary ergodic methods.
Gesehen am 13.07.2022
Dedicated to Prof. Claude Viterbo on the occasion of his 60th birthday